Efficacy and safety of traditional chinese medicine treatment for overweight and obese individuals: A systematic review and meta-analysis - Wen, Zhi Ge; Zhang, Qi Qi; Zhang, Li Li; Shen, Meng Fei; Huang, Yi Shan; Zhao, Lin Hua (Frontiers in Pharmacology, 2022)
Background: The prevalence of obesity is increasing worldwide, causing it to become a global health issue. Traditional Chinese medicine (TCM) used in the treatment of overweight/obesity have been widely implemented in clinical practice, but its overall efficacy and safety remain unclear. This review aims to evaluate the effectiveness and safety of TCM based on randomized controlled trials (RCTs). Methods: A systematic review was conducted by searching PubMed, Cochrane Library, Web of Science, Embase and Clinical Trails from their inception to March 2021. Two reviewers screened studies, extracted the data and assessed risk of bias independently. The data were pooled for meta-analysis or presented narratively. Results: Twenty-five RCTs involving 1, 947 participants were included. Compared with placebo or blank control, TCM treatment reduced Body Mass Index (BMI) (MD = -0.99; 95% confidence interval (CI) = -1.25, -0.73; I2 = 38%), reduced weight (MD = -2.32, 95%CI = -2.85, -1.80; I2 = 40%), reduced waist circumference (MD = -2.60; 95%CI = -3.35, -1.84; I2 = 0%), reduced hip circumference (MD= -3.48; 95%CI = -4.13, -2.83; I2 = 0%), reduced total cholesterol (TCHO) (MD = -10.45; 95%CI = -18.92, -1.98; I2 = 63%), reduced triglycerides (TG) (MD = -4.19; 95% CI = -6.35, -2.03; I2 = 25%), increased high-density lipoprotein (HDL) (MD = -3.60; 95% CI = -6.73, -0.47; I2 = 81%), reduced fasting blood glucose (FBG) (MD = -0.77; 95%CI = -1.24, -0.29; I2 = 91%). Glycated hemoglobin (HbA1c)、body fat、low-density lipoprotein (LDL) were not statistically significant. For people with hypertension, decreased systolic blood pressure (SBP) (MD = -5.27; 95% CI = -8.35, -2.19; I2 = 58%), decreased diastolic blood pressure (DBP) (MD = -4.30; 95% CI = -5.90, -2.69; I2 = 0%). For people with normal blood pressure, there was no significant change. There was no significant difference in liver function. Conclusions: It has been demonstrated that TCM has good clinical efficacy and safety in the treatment of overweight/obesity. TCM may be suitable for overweight/obesity in adult populations for its efficacy and safety of long-term treatment.